2014
DOI: 10.1155/2014/386721
|View full text |Cite
|
Sign up to set email alerts
|

GARCH‐Type Model with Continuous and Jump Variation for Stock Volatility and Its Empirical Study in China

Abstract: On the basis of GARCH-RV-type model, we decomposed the realized volatility into continuous sample path variation and discontinuous jump variation, then proposed a new volatility model which we call the GARCH-type model with continuous and jump variation (GARCH-CJ-type model). By using the 5-minute high frequency data of HUSHEN 300 index in China, we estimated parameters of the GARCH-type model, the GARCH-RV-type model, and the GARCH-CJ-type model and compared the three types of models’ predictive power to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“… Few studies (Koopman, Jungbacker, & Hol, 2005; Zhang & Lan, 2014) examine the presence of jumps in GARCH‐RV‐type models. For example, Zhang and Lan (2014) show that GARCH‐RV type models accounting for jumps have more power to predict the future volatility of stock prices than other GARCH‐RV type approaches. …”
mentioning
confidence: 99%
“… Few studies (Koopman, Jungbacker, & Hol, 2005; Zhang & Lan, 2014) examine the presence of jumps in GARCH‐RV‐type models. For example, Zhang and Lan (2014) show that GARCH‐RV type models accounting for jumps have more power to predict the future volatility of stock prices than other GARCH‐RV type approaches. …”
mentioning
confidence: 99%
“…In addition, comparing the results of this study with other studies such as the study of Koutmos (2012) also shows similar result that models which use earnings ratio will mostly yield a positive relationship. The study of Zhang and Lan (2013) also finds that the model with the effect of realized volatility would provide better accuracy. In this study, the results of model 2 are significantly more effective than the results of model 1.…”
Section: Discussionmentioning
confidence: 98%
“… Source: The authors. Notes: *Continuous sample path variation and discontinuous jump variation are computed by using realized volatility concept (Zhang & Lan, 2013). (Example of the computation is shown in Appendix B.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the study of volatility, scholars have focused on the GARCH models. Under different hypothesis distributions, Zhang and Lan [5] gave the GARCH-type model with continuous and jump variation for stock volatility and its empirical study in China. Zhou et al [6] studied the measurements accuracy of VaR based on GARCH models using spot transactions in Shanghai and London gold markets as objects, and they concluded that the Shanghai gold market was more risky than the London gold market.…”
Section: Introductionmentioning
confidence: 99%